Keanekaragaman Burung di Kawasan Mangrove dan Tambak Setapuk Singkawang Kalimantan Barat - Rahmadani, Muhammad Alif (Jurnal Pendidikan Biologi Undiksha, 2023)
Birds have a wide range of habitats and are found in water and terrestrial areas, one of which is the mangrove area. The Setapuk Mangrove area has potential tourist attractions that can be developed, such as hearing birds chirping. The Setapuk Mangrove area has just been rehabilitated and has become an ecotourism area which has the potential to be used to improve the community's economy and preserve the environment. The aim of this research is to determine the diversity of birds in the Setapuk Singkawang Mangrove Area, West Kalimantan. This research was carried out from October to November 2023. Bird diversity research was carried out in 2 locations, namely mangrove locations and ponds using the Concentration Count method. Each location creates 3 points with a point size of 100 m. The results of this research found 14 species in the Setapuk mangrove area. The largest number of individuals in the morning mangrove location was C. leschenaultia (Great Sand Plover). In the afternoon mangroves that are often found are G. alba (White Sea Tern). In the pond locations in the morning and evening, the most numerous individuals were O. ruficeps (Cinenen Gray). The highest diversity is found in pond locations with a value of 1.67 while in mangrove locations it is 1.60. The Dominance Index at the pond location is 0.23 and the mangrove has a value of 0.26, and the Evenness Index value for the pond location is 0.70 and the mangrove location is 0.67.